Analysing the international civil liability regime for oil pollution damage caused by ships and aligning with it the South African civil liability regime for oil pollution damage cause by ships - Moodley, Alecia Genise (Department of Public Law, 2019)
Oil-fouled beaches, dying seabirds and severe economic loss from the closure of fishing grounds and holiday resorts is the picture painted by oil spills, and these consequences often arouse public outrage. Oil spills cause extensive damage to the marine environment and to human society. Indeed, the economic consequences are often extensive, and it is for this reason that the internationalisation of a civil liability regime for oil pollution damage was initially proposed. The first move towards an international civil liability regime came when states which were affected by an unprecedented oil spill made it clear that individual states could not cope alone with these negative effects. The tanker held responsible for the oil spill which has been described as ‘the greatest peace-time menace ever to have confronted Britain’s shores’ was Liberian-registered tanker, the Torrey Canyon About 6 000 nautical miles south of Pollard rock, which was struck by the Torrey Canyon in 1967, lays the Cape of Good Hope, South Africa (SA). The route that runs through the Cape of Good Hope is one of the busiest oil tanker routes in the world and this contributes to the large volume of oil traffic in this route. The Cape of Good Hope is also known as the ‘Cape of Storms’ and many vessels have faltered off this hazardous coastline of SA. The 1973 International Convention for the Prevention of Pollution From Ships, as modified by the Protocol of 1978 (MARPOL 73/78) to address pollution prevention, the 1969 Intervention Convention to deal with emergency response, the 1969 International Convention on Civil Liability for Oil Pollution Damage (1969 CLC), and the 1971 International Convention on the Establishment of an International Fund for Compensation for Oil Pollution Damage (1971 Fund convention) were enacted after the Torrey Canyon disaster, once it was clear that the international regime was not sufficient to deal with such an immense oil spill. 8 In addition, and of paramount importance, is the 1982 United Nations Convention on the Law of the Sea (UNCLOS) which is known as the “framework” or ”umbrella” convention in the international law of the sea. The purpose of this dissertation is to analyse and compare the International and the South African civil liability regimes on oil pollution damage caused by ships. This comparative analogy will be done with the view of ascertaining whether the legal regime of South Africa (SA) is in line with the international civil liability regime and to ascertain what improvements can be made to SA’s civil liability regime. During this analysis, any inadequacies identified in these regimes will be addressed briefly. South Africa gave effect to the 1969 CLC and the 1971 Fund convention by enacting the Marine Pollution (Control and Civil Liability) Act 6 of 1981 (MPA)(own emphasis). SA, however, only acceded to the 1992 protocols of amendment on 1 October 2005 (own emphasis) and, subsequently, did not implement these amendments domestically. Eight years later, the government finally updated the domestic law by providing for the domestic enactment of the provisions as contained in the 1992 protocols. In December 2013 (own emphasis), the Merchant Shipping (Civil Liability Convention) Act 25 of 2013 (“MSCLC act”), the Merchant Shipping (International Oil Pollution Compensation Fund) Act 24 of 2013 (“the IOPC act”), the Merchant Shipping (International Oil Pollution Compensation Fund) Administrations Act 35 of 2013 (“Administrations act”), and the Merchant Shipping (International Oil Pollution Compensation Fund) Contributions Act 36 of 2013 (“Contributions act”) was enacted by Parliament. This dissertation serves to explore these laws of SA against the backdrop of the relevant international conventions including the UNCLos which provides a general framework. Prior to these amendment laws, SA’s regime was outdated and provided insufficient compensation for a major oil spill. The primary research question of this dissertation is: Is SA’s civil liability regime consistent with, aligned with and adequate in light of, the international civil liability regime? In order to answer the abovementioned research question, this dissertation adopts the following structure: It is divided into five chapters which will follow one another as the civil liability regime is being unpacked and analysed. Chapter 1 contains an introduction, background, and sets out the scope and limits of this topic; It furthermore provides a brief literature review on civil liability to aid in understanding the main topic of this dissertation. In Chapter 2 it will be beneficial to look at the brief history behind the international regulation of marine oil pollution in order to grasp the reasoning behind the existing international regime. Therefore, the international history will first be addressed, and thereafter a comprehensive analysis of the various conventions that make up the international regime will be done. There will also be an indication of certain inadequacies which may be contained therein, before concluding and moving the focus to SA in the next chapter. It will then be of importance to address SA’s liability regime critically. In Chapter 3 the new marine pollution acts are dissected whilst keeping in mind the broad themes that originate in the international conventions. This third chapter also addresses whether the MSCLC act has strengthened the South African regime and whether SA will have access to the compensation funds after the enactment of the IOPC Fund Act. Chapter 4 will accordingly look at the laws of general application in SA with a view of ascertaining how these laws complement the civil liability regime and how reliance on them could improve the South African regime. Furthermore, recommendations will be made with regards to improving SA’s regime. Finally, this dissertation will come to a conclusion in Chapter 5 which will also briefly summarise the findings of the previous chapters.